2009
DOI: 10.1002/jor.20954
|View full text |Cite
|
Sign up to set email alerts
|

Axin2 regulates chondrocyte maturation and axial skeletal development

Abstract: Axis inhibition proteins 1 and 2 (Axin1 and Axin2) are scaffolding proteins that modulate at least two signaling pathways that are crucial in skeletogenesis: the Wnt/b-catenin and TGF-b signaling pathways. To determine whether Axin2 is important in skeletogenesis, we examined the skeletal phenotype of Axin2-null mice in a wild-type or Axin1 þ/À background. Animals with disrupted Axin2 expression displayed a runt phenotype when compared to heterozygous littermates. Whole-mount and tissue b-galactosidase stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 35 publications
3
32
2
Order By: Relevance
“…By this approach, we found that collagen X and MMP-13 expressions were significantly increased following LiCl-induced β-catenin activation. It is well known that articular chondrocytes undergo maturation during early OA pathogenesis, after which the characteristic maturational marker genes collagen X [28][29][30] and MMP-13 [31,32] are expressed. MMP-13 is a potent enzyme that preferentially targets type II collagen in the cartilage matrix for degradation; interestingly, MMP-13 expression has been found to be increased in human OA joints [33].…”
Section: Discussionmentioning
confidence: 99%
“…By this approach, we found that collagen X and MMP-13 expressions were significantly increased following LiCl-induced β-catenin activation. It is well known that articular chondrocytes undergo maturation during early OA pathogenesis, after which the characteristic maturational marker genes collagen X [28][29][30] and MMP-13 [31,32] are expressed. MMP-13 is a potent enzyme that preferentially targets type II collagen in the cartilage matrix for degradation; interestingly, MMP-13 expression has been found to be increased in human OA joints [33].…”
Section: Discussionmentioning
confidence: 99%
“…Further assessment of these mice revealed an important role of axin-2 in mature bone: significant differences in bone volume and BMD are seen at 6 and 12 months when compared with wild-type mice, but no differences in bone volume or BMD are observed at 2 months of age (129). These mice also show an abnormal chondrocyte phenotype due to expedited maturation, resulting in a shorter hypertrophic zone in the growth plate of long bones (128). An Axin2 mutation was also identified in the canopus (canp) mouse: mice that were homozygous for the V26D missense mutation in Axin2 were arrested at midgestation with abnormal heart development and shortened or doubled tails.…”
Section: Axinmentioning
confidence: 95%
“…Removal of the Wnt antagonist secreted Frizzled-related protein 1 (sFRP1) in mice led to a diminished growth plate and increased calcification in the hypertrophic zone, and accelerated differentiation of hypertrophic chondrocytes (Gaur et al 2006). A similar phenotype is seen in Axin2-null mice that were runted and showed evidence of accelerated chondrocyte maturation (Dao et al 2010). Constitutive activation of b-catenin in chondrocytes and skeletal mesenchyme also caused neonatal lethality with severe chondrodysplasia (Akiyama et al 2004;Guo et al 2004;Hill et al 2005).…”
Section: Wnt/b-catenin Signaling In Cartilage and Synovial Joint Formmentioning
confidence: 97%
“…This phenotype can be rescued by reducing levels of b-catenin (Liu et al 2007). Compound Axin2 2/2 ; Axin1 þ/2 mice have recently been shown to develop severe craniofacial and axial skeleton defects (Dao et al 2010), again highlighting the important pro-osteogenic functions of the Wnt/b-catenin signaling pathway in skeletal development.…”
Section: Wnt/b-catenin Signaling In Osteoblast Functionmentioning
confidence: 99%